Assessment of shoreline changes and associated erosion and accretion pattern in coastal watersheds of Tamil Nadu, India - Leo George Sekar; X. Androws; K. Annaidasan; Ashish Kumar; R. Kannan; G. Muthusankar; K. Balasubramani (Natural Hazards Research, 2024)
The coastal region is not a constant and depends on several physical elements. Analogous to the world trend, the coastal areas of Tamil Nadu are encountering sea level rise and associated shoreline changes. However, the rate of change is not uniform and varies considerably. The study revealed such differences in shoreline changes during the past 30 years and identified erosion and accretion patterns trends in Tamil Nadu's coastal watersheds, from Pulicat (Thiruvallur district) to Kodyar (Kanyakumari district). The study used remotely sensed Landsat TM (Thematic Mapper) and OLI (Operational Land Imager) datasets to analyse shoreline changes from 1988 to 2018. The Digital Shoreline Analysis System (DSAS) tool is used to derive trends of shoreline changes by End Point Rate (EPR) and Net Shoreline Movement (NSM). The mean EPR is- 0.26 ​m/yr and NSM is-8.03 ​m/yr, suggesting the overall shoreline of the Tamil Nadu coast is shifting landward. However, the annual rates of EPR and NSM vary considerably from watershed to watershed, and therefore, these indices were used to categorise the coastal watersheds based on erosions and accretions. The results identified a high erosion rate in the watersheds of Coleroon, Arasalar (Nagapattinam), Gundar (Ramanathapuram), Vembar, Lower Vaippar (Thoothukkudi), Nambiyar, Hanuma (Tirunelveli), and Putian, Kodyar (Kanyakumari). Field surveys were conducted to verify ground conditions at 139 random locations along the 1000 ​km shoreline stretch. About 75% of respondents said they experience a very high to high risk of coastal erosion. The rates estimated by the study and categorisation of the coastal watersheds could be most helpful in evaluating the cumulative impact of coastal hazards and preparing sustainable development plans. The outcomes may also help to create awareness in more susceptible areas.